2018
DOI: 10.3390/ijms19020558
|View full text |Cite
|
Sign up to set email alerts
|

Recent Updates on Treatment of Ocular Microbial Infections by Stem Cell Therapy: A Review

Abstract: Ocular microbial infection has emerged as a major public health crisis during the past two decades. A variety of causative agents can cause ocular microbial infections; which are characterized by persistent and destructive inflammation of the ocular tissue; progressive visual disturbance; and may result in loss of visual function in patients if early and effective treatments are not received. The conventional therapeutic approaches to treat vision impairment and blindness resulting from microbial infections in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 215 publications
(348 reference statements)
0
6
0
1
Order By: Relevance
“… 10 The production of virulence factors such as proteases, lipases, enterotoxins, and hemolysins by B. cereus causes endophthalmitis, retinal layer folding, and detachment within 12 hours and complete central visual loss or even entire eye loss, which often occurs within 2 days. 23 , 24 It has been reported that in posttraumatic B. cereus endophthalmitis, more than 70% of patients lost some degree of vision in the infected eye, as few as 9% of those retained a visual acuity of 20/70 or better, and 48% of patients had eyeball enucleation, making it one of the most severe forms of bacterial endophthalmitis. 10 , 20 , 25 In our study, a 6-year-old child injured by a firecracker explosion was also diagnosed with B. cereus endophthalmitis during the operation and underwent vitrectomy combined with intravitreal antibiotic (vancomycin) injection 16 hours after the injury, and finally, the visual acuity improved to 20/25.…”
Section: Discussionmentioning
confidence: 99%
“… 10 The production of virulence factors such as proteases, lipases, enterotoxins, and hemolysins by B. cereus causes endophthalmitis, retinal layer folding, and detachment within 12 hours and complete central visual loss or even entire eye loss, which often occurs within 2 days. 23 , 24 It has been reported that in posttraumatic B. cereus endophthalmitis, more than 70% of patients lost some degree of vision in the infected eye, as few as 9% of those retained a visual acuity of 20/70 or better, and 48% of patients had eyeball enucleation, making it one of the most severe forms of bacterial endophthalmitis. 10 , 20 , 25 In our study, a 6-year-old child injured by a firecracker explosion was also diagnosed with B. cereus endophthalmitis during the operation and underwent vitrectomy combined with intravitreal antibiotic (vancomycin) injection 16 hours after the injury, and finally, the visual acuity improved to 20/25.…”
Section: Discussionmentioning
confidence: 99%
“…e study reported high rates of AMR, particularly among the Staphylococci species [17]. Ocular diseases, if not treated properly, can cause irreversible damage to the structures of the eye, leading to visual impairment and blindness [18]. Drug-resistant bacteria and the high prevalence of ocular bacterial infections in pediatric patients stress the importance of knowing the causative microorganisms and antimicrobials susceptibility profile.…”
Section: Introductionmentioning
confidence: 99%
“…Patents related to the prevention & treatment of ocular infections & novel ocular drug delivery technologies [91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107] are depicted in Table 3. [107]…”
Section: Antibiotics and Antimicrobialsmentioning
confidence: 99%